Numerical Modeling of Flow Conditions during Steel Filtration Experiments. Issue 9 (3rd July 2017) - Asad, Amjad; Werzner, Eric; Demuth, Cornelius; Dudczig, Steffen; Schmidt, Anne; Ray, Subhashis; Aneziris, Christos G.; Schwarze, Rüdiger
Abstract : In the present article, the performance and the efficiency of ceramic filters for continuous steel filtration in an induction crucible furnace, which is part of the steel casting simulator facility located at Technische Universität Bergakademie Freiberg, is investigated numerically. In order to achieve this objective, a macro‐scale simulation for the melt flow in the crucible is coupled with a pore‐scale simulation for the flow inside the ceramic filter that is adequately resolved by its detailed filter geometry, obtained from computed tomography scan images. The considerable influence of the filter on the flow field is indicated from the present results. Moreover, the efficiency of the employed filter is also determined and compared for two pore densities. Abstract : Numerical simulations are performed in order to determine the filtration efficiency of ceramic filters in an induction crucible furnace. Both pore‐scale and macro‐scale simulations are coupled in order to achieve this task. The considerable influence of the filter on the flow field is shown in the present article. Moreover, it is indicated that the filtration efficiency of the filters depends on the pore density of the filters.